Aging of a dielectric fluid used for direct contact immersion cooling of batteries - Daccord, Rémi; Kientz, Thiébaut; Bouillot, Alexandre (Frontiers in Mechanical Engineering, 2023)
Batteries of electric vehicles require appropriate cooling to allow for increased performances such as high energy density and fast charging capabilities. Immersion of the cells in a dielectric fluid provides substantial benefits in terms of safety and performance, but the selection of a relevant coolant remains a complex task. This paper reviews the fluid properties which are considered most significant for this application, and provides an experimental comparison of the key properties of one fluid candidate under various aging conditions devised to reproduce several years of operation in a vehicle.